HERITAGE TOURISM: A BIBLIOMETRIC ANALYSIS OVER THREE DECADES (1994-2023) - Jaime José ORTS-CARDADOR; Jesús Claudio PEREZ-GALVEZ; Gema María Gómez-Casero FUENTES; Carol Angélica Jara ALBA (Geo Journal of Tourism and Geosites)
This qualitative study explores the relationship between tourism and places recognized by UNESCO as World Heritage Sites, whether tangible (WHS) or intangible (ICH). In the last two decades there has been a growth in the number of resources with UNESCO recognition. It aims to fill the research gap in the analysis of heritage tourism using bibliometric techniques. Data were collected from 886 documents in the period 1994-2023 (December) from the Web of Science database. Using the VOSviewer software, scientific maps were created showing the current and future line of research in this scientific field. The results show evidence of related research on Tourism sustainability at UNESCO sites in China and Tourism sustainability of cultural heritage for the whole period. In addition, two new research topics from 2016 are identified: Motivation and satisfaction of heritage tourists and Authenticity of intangible heritage. The results help to visualise the structure and trends of heritage tourism research, which can help researchers, policy makers and destination marketing organisations (DMOs) to gain knowledge and understanding of existing studies and current research topics.